2015
DOI: 10.5897/err2015.2195
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers motivations toward teaching profession and their opinions about the pedagogic formation program

Abstract: The present study aimed to investigate pre-service teachers' motivations toward teaching profession and their opinions about pedagogical formation program. In this study descriptive and correlational research methods were used. It was carried out with (a) graduate students doing a master's program without thesis, (b) undergraduate students participating in the pedagogic formation program. The total number of participants was 301. The data were collected using an evaluation scale for pre-service teachers doing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Hasan et al [32] investigated student teachers' motivations toward the teaching profession and their views about professional development programs. The data for the study were collected from 302 student teachers using a questionnaire, and the subjects of the study expressed their motivation and interest in being teachers due to intrinsic and preferential tendencies.…”
Section: -Introductionmentioning
confidence: 99%
“…Hasan et al [32] investigated student teachers' motivations toward the teaching profession and their views about professional development programs. The data for the study were collected from 302 student teachers using a questionnaire, and the subjects of the study expressed their motivation and interest in being teachers due to intrinsic and preferential tendencies.…”
Section: -Introductionmentioning
confidence: 99%
“…It was observed that preservice teachers' motivation contributes much to their teaching. In a study conducted by Hasan et al (2015), the excitement of preservice teachers for teaching subjects in their domains and their positive teaching experiences are essential sources of motivation and efficacy for the teaching profession. Efficacy in teaching means a teacher's belief in their ability to help students succeed.…”
Section: Introductionmentioning
confidence: 99%